Isolation, identification, and detection of ACC deaminase gene-encoding rhizobacteria from rhizosphere of stressed pineapple - Dori Kusuma Jaya; Giyanto Giyanto; Novik Nurhidayat; Sarjiya Antonius (Universitas Gadjah Mada, 2019)
ACC deaminase is a microbial cytoplasmic enzyme that cleaves ACC, a precursor of ethylene, in the stressed plant. The aims of this study were to isolate, identify, and detect the presence of ACC deaminase gene-encoding rhizobacteria from the rhizospheric soil of pineapple plants that have been exposed to abiotic and biotic stress, specifically herbicide, flooding, and Phytophthora spp. stress. A total of 49 rhizobacterial isolates were obtained, seven of which were observed for their growth on DF medium containing 3 mM L-1 ACC. The four best-growing isolates were selected for genomic DNA extraction. They were molecularly identified as Stenotrophomonas maltophilia (3), Burkholderia territorii (2A), Pseudomonas oryzihabitans (5B), and Bacillus tropicus (1E). A set of primers, 105F-acdS 5’-TGCCAAGCGTGAAGACTGC-3’ and 244R-acdS 5’-GGGTCTGGTTCGACTGGAT-3’, were constructed to amplify the ACC deaminase gene (acdS). Based on melt peak curve analysis, four products appeared to show a specific single peak at 86, 89, 87, and 89.5°C, indicating a single product was produced. In addition, a Blast search showed that these four products met the ACC deaminase feature and their acdS sequences were clustered into an ancestral group compared with the bacterial strains deposited in GenBank. These results suggest that ACC deaminase gene-encoding rhizobacteria from a pineapple plantation of tropical origin may affect the acdS sequences and may contribute to the host plant’s stress tolerance.